Groundwater markets in east coast of Puducherry Union Territorry: analysis of pricing and irrigation efficiency - K Kannan; Pouchepparadjou A; Anil Kuruvila; Shaik Allaudin A (Agricultural Economics Research Review, 2023)
This paper examines structure, determinants and efficiency of groundwater markets and suggest policy measures to contain over-extraction of groundwater in the Union territory of Puducherry on east coast of India. The analysis of structure of groundwater market shows a large proportion (82%) of the farmers entering into one or the other activities related to water market. The number of water buyers decreases with increase in farm size, while the number of sellers increases with the increase in farm size. The analysis of conduct of groundwater markets reveals a seller- buyer concentration ratio of 1:2.39. The farmers having less operational landholdings, higher fragmented landholdings and low capacity water lifting device have a higher probability of buying groundwater. Further, selling of groundwater is more concentrated among farmers with large operational holdings, less fragmentation and joint ownership of a modern water extraction mechanism (WEM). Resource use efficiency analysis indicates a close association between increased productivity and better irrigation management due to ownership of the modern WEMs. The Nash equilibrium framework used to study the bargaining power brings out that the level of irrigation of buyers and sellers as key factors in price determination in groundwater market. The selling price of groundwater is found markedly higher than the total cost of water extraction, implying exploitative nature of groundwater markets.